Use of special exercises to intensify speed and strength loads in the training of student volleyball teams - Yatskovets, A. S.; Gabov, M. V.; Ponimasov, O. E.; Shelkova, L. N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to improve the physical and technical training of volleyball players through the use of special speed and strength exercises.